2020
DOI: 10.1038/s41586-020-2933-1
|View full text |Cite
|
Sign up to set email alerts
|

Discoveries in structure and physiology of mechanically activated ion channels

Abstract: The ability to sense physical forces is conserved across all organisms. Cells convert mechanical stimuli into electrical or chemical signals via mechanically activated ion channels. In recent years, the identification of new families of mechanosensitive ion channels, such as PIEZO and OSCA/ TMEM63 channels, along with surprising insights into well-studied mechanosensitive channels have driven further developments in the mechanotransduction field. Several well-characterized mechanosensory roles such as touch, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
314
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 408 publications
(327 citation statements)
references
References 152 publications
9
314
0
4
Order By: Relevance
“…Beyond bacteria, eukaryotic cells also have the ability to transduce mechanical signals into cellular responses, regulating an array of physiological processes including development, immunity and touch sensation 33 . Eukaryotic cell motility is also sensitive to mechanical cues.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond bacteria, eukaryotic cells also have the ability to transduce mechanical signals into cellular responses, regulating an array of physiological processes including development, immunity and touch sensation 33 . Eukaryotic cell motility is also sensitive to mechanical cues.…”
Section: Discussionmentioning
confidence: 99%
“…Two gating models -the force-from-lipids and the force-from-filament model -are commonly used to explain how mechanical forces exerted on a cell are transmitted to mechanically-gated ion channels embedded in the plasma membrane. The force-fromlipids model proposes that mechanical stimuli cause changes in the transbilayer pressure profile, which supposedly lead to conformational changes and thus activation of the channel, whereas the force-from-filament model suggests that mechanical forces are transmitted to the channel by the cytoskeleton either via direct interactions of via intracellular tethers 31,33 . While it was convincingly demonstrated that PIEZO1 is activated by force-from-lipids under experimental conditions in which the cytoskeleton is either completely missing (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Most researchers in the field, however, favor an alternative explanation and proposed that the cytoskeleton indirectly transmits forces to the channel by generating local membrane tension via interactions with other membrane proteins, such that the ultimate stimulus that activates PIEZOs is force-from-lipids (Fig. 5l) 3,15,[31][32][33] . Accordingly, this hypothesis implies that a channel with normal force-from-lipids sensitivity would also respond normal to membrane indentation in cells with an intact cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations